TRADITIONAL LAND USE BY THE ASHÃNINKA PEOPLE OF WESTERN AMAZONIA - Righi, Ciro Abbud; RÃos GÃ¡lvez, VÃctor Alan (REVISTA DE AGRICULTURA, 2019)
The depreciation of the traditional production systems and consequent cultural de-characterization of indigenous societies with the standardization of agriculture make urgent to understand their land use systems. The information collected has the potential to lead for more sustainable land-use-systems without imposing technological packages. The objective of the present work was to document the production systems and territorial use practiced by the Asháninka people in the Peruvian Amazon. Two agricultural systems are practiced: slash and burn, and sandbank- seasonal cultivation of areas along the rivers. Hunting, fishing, and collection of native fruits complement their subsistence diet. The slash-and-burn agriculture is performed on small plots, up to 2 ha, of forest land mainly in secondary regeneration (purma – in the Asháninka language) due to ease of management. The fallow period is short (5 years) which may be leading to soil impoverishment. Studies of nutrient cycling will be necessary to evaluate the impact. There is a need for studies to improve traditional farming systems considering not only the potential gains in productivity, but also the maintenance of their cultural identity.